If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 9 = 3z + -1 Reorder the terms: 9 + 5x = 3z + -1 Reorder the terms: 9 + 5x = -1 + 3z Solving 9 + 5x = -1 + 3z Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 5x = -1 + -9 + 3z Combine like terms: 9 + -9 = 0 0 + 5x = -1 + -9 + 3z 5x = -1 + -9 + 3z Combine like terms: -1 + -9 = -10 5x = -10 + 3z Divide each side by '5'. x = -2 + 0.6z Simplifying x = -2 + 0.6z
| -4+6(8X+2)=296 | | 121x^4-81=0 | | 7+2(6)= | | -3(9r+4)= | | .15w=45 | | Q+14=8q+7 | | -15=-4(3)+3 | | 3x^2-10+x=0 | | 64n^2+16n+1=0 | | 1x+2=2 | | -8m+-9(5+-3m)=12 | | -6X+2=-28X | | 3x^2-16-4=0 | | 8(x+7)=6x+74 | | 15x-10=x+4 | | 7s^2-2s-5=0 | | 14x+(3x+2)*(x-5)=0 | | 7z=2.1 | | 15r-18r=687 | | 5x+29=-7 | | 8(x+8)=6(x+80) | | 3--6/6+4= | | 11=-4(2)+3 | | 6x-3=18x | | -12-9= | | 6x-3=23x | | -1/5(-1/3)= | | 43+n=-50 | | 6x^2-36x-96= | | 5(r-7)= | | 5(6x+7)= | | 14x+3x^2-13x-10=0 |